Book review: Sarah Easterby-Smith, Cultivating Commerce: Cultures of botany in Britain and France, 1760–1815 . Cambridge, Cambridge University Press, 2017 - Harris, S (Oxford University Press, 2018)
We are surrounded by plants that are not native to the countries in which we live. Some are accidental arrivals but many are deliberate introductions. The first step in the introduction process is the collection of a plant sample. Stating a handful of seeds or dried plant specimens was taken from their native habitat and transferred to a garden or herbarium oversimplifies intricate, complex networks of interpersonal relationships. Fascination with these networks and the long-term environmental, social, biological, economic or political consequences of plant movement and establishment unites researchers across diverse academic disciplines.